Morphological structure of silica sulfuric acid and Nafion composite membrane using electrostatic force microscopy. (17th August 2021) - Kwon, Osung; Oh, Kwangjin; Park, JaeHyoung; Park, Sam; Lee, Tae Gwan; Son, Byungrak
Summary: In this study, the proton conductivity enhancement mechanism of Nafion–silica sulfuric acid (SSA) composite membranes was studied using the vibrating tip technique of atomic force microscopy. The Nafion–SSA composite membranes showed enhanced proton conductivity and thermal and mechanical properties compared to those of pristine Nafion. Among the selected different weight percentages of SSA, 1 wt% SSA had the highest values. The aim of this study was to understand how proton conductivity enhancement is related to structure and morphology. It was determined that the enhancement is related to a microscopic morphological structure, which is the separation of the hydrophilic ionic channel network and hydrophobic backbone. The morphologies of membranes of three different weight percentages were studied using noncontact mode atomic force microscopy, force–distance spectroscopy, and electrostatic force microscopy to understand the ionic domain structures. Several factors that influence the proton conductivity enhancement of the composite membranes were investigated, including water content, hydrophilicity, and ionic domain enhancement due to the interconnection of the SSA and ionomer. Among the different SSA weight percentages, the 1 wt% Nafion–SSA composite membrane demonstrated superior performance. It presented the highest energy dissipation, water content, and phase separation. This result implied that 1 wt% SSA optimally induced phase separation owing to the interaction with the sulfonic acid groups of the SSA and reorganization of the morphological structure compared with other weight percentages of Nafion–SSA composite membranes.